Intrathecal Isobaric Levobupivacaine Versus Isobaric Ropivacaine for Infra-Umbilical Surgeries - Md Nishat Akhtar; Ahmad, Shazia; Ilahi, Ikram (Academia Anesthesiologica International, 2020)
Background: The aim is to compare intrathecal isobaric levobupivacaine versus isobaric ropivacaine for infra-umbilical surgeries. Subjects & Methods: Sixty- eight patients of either gender of American Society of Anaesthesiologists (ASA) class I, II or III scheduled for infra-umbilical surgery were included. Patients were divided into 2 groups of 34 each. Group A received isobaric levobupivacaine (0.5%, 0.3-0.4 mg/kg), whereas group B received isobaric ropivacaine (0.5%, 0.5 mg/kg) intrathecally. Results: Mean age as 34.5 years in group I and 36.2 years in group II, there were 14 males and 20 females in group I and 18 male and 16 females in group II. The mean weight was 56.2 Kgs inn group I and 53.1 Kgs in group II and duration of surgery was 37.4 minutes in group I and 38.0 minutes in group II. Sensory block onset (min) was 2.14 and 2.65, duration of sensory block (min) was 254.6 and 210.2, complete sensory block (min) was 5.28 and 6.12, 2-segment regression time (min) was 87.1 and 80.2, onset of motor block (min) was 2.30 and 3.52, complete motor block (min) was 10.2 and 12.3, duration of motor block (min) was 204.5 and 102.6 and duration of analgesia (min) was 273.4 and 232.8. A significant difference was observed (P< 0.05). Conclusion: Intrathecal isobaric levobupivacaine and ropivacaine with fentanyl produces effective surgical anaesthesia and postoperative analgesia.